PENGARUH TERAPI KOGNITIF TERHADAP TINGKAT KECEMASAN PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Nurjanah, Dian Eka (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Individuals with long- term hemodialysis often feel anxious about the pain condition that cannot be foreseen and disruption in their lives. The results of the survey conducted in hospitals Hemodialysis Space M. Yunus Bengkulu on 10 samples obtained, 6 of them experienced moderate anxiety and 4 patients experienced mild anxiety. The purpose of the study was to determine the effect of cognitive therapy on anxiety of patients with chronic renal failure undergoing hemodialysis therapy. This research is Pre Experimental design one group pretest-posttest. The population in this study were all patients with chronic renal failure undergoing hemodialysis therapy Hemodialysis Hospital in Space M. Yunus Bengkulu, which is 184 people . Samples taken by accidental sampling as many as 30 patients with chronic renal failure undergoing hemodialysis therapy . Data collected by direct interview to the patient. Data analysis was performed using univariate and bivariate Paired t-test at α 5 %. The results showed that the average anxiety patient with chronic renal failure undergoing hemodialysis therapy prior to cognitive therapy was 9.33 , while the average anxiety after cognitive therapy was 6.6. There was an average difference of anxiety before and after cognitive therapy , and there was a significant decrease between the average anxiety after cognitive therapy cognitive therapy than before in patients with chronic renal failure undergoing hemodialysis therapy Hemodialysis Hospital in Space M. Yunus Bengkulu ( p value = 0.000 ).